USE OF AND ATTITUDES TOWARD TOBACCO AND ALCOHOL AMONG ADULTS IN SOUTHERN SRI LANKA - Lombardo, Sarah (2013)
The adverse health effects of tobacco and alcohol are well known. Alcohol consumption is increasing in Sri Lanka, but few population studies have been conducted. The objective of this study was to document tobacco and alcohol consumption levels among adults in southern Sri Lanka and to identify the main reasons for using or refraining from alcohol and tobacco products. Tobacco and alcohol use within Sri Lanka is relatively common, particularly among adult males. Reasons given for smoking and drinking frequently relate to social and image-based motivators. Women may be especially susceptible to the influence of peer pressure in social situations. Public health efforts should consider the use of demographic-specific anti-tobacco and anti-alcohol messages, as the motivators driving behavior appear to differ across gender and age groups.